Outcomes of Operative Vaginal Delivery during Trial of Labor after Cesarean Delivery - Brock, Clifton O.; Govindappagari, Shravya; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2017)
Objective The objective of this study is to determine the maternal and neonatal morbidity associated with attempting operative vaginal delivery (OVD) compared with the alternative of a laboring repeat cesarean delivery (LRCD) in women attempting a trial of labor after cesarean delivery (TOLAC).Methods This is a secondary analysis of a multicenter prospective study designed to assess perinatal outcomes of OVD in women with a prior uterine scar. The study includes women who attempted TOLAC and reached +2 station with a fully dilated cervix. Composites on neonatal and maternal morbidity were compared between women in whom OVD was attempted and those who underwent LRCD by fitting multivariate logistic regression models.Results In total, 6,489 women attempting TOLAC reached 2+ station with a fully dilated cervix. Of these, 5,640 (86.9%) had a spontaneous vaginal delivery, 762 (11.7%) underwent attempted OVD, and 87 (1.3%) had an LRCD. Compared with attempting OVD, LRCD was associated with greater neonatal morbidity (odds ratio [OR]: 2.41; 95% confidence interval [CI]: 1.13–5.15) and less maternal morbidity (OR: 0.28; 95% CI: 0.14–0.55). Maternal morbidity of OVD is driven by perineal injury.Conclusion In laboring women with a previous uterine scar, attempting OVD is associated with greater maternal and less neonatal morbidity than LRCD.
Keywords: VBAC; cesarean delivery; vacuum-assisted delivery; forceps-assisted delivery